Epilepsy in families: Age at onset is a familial trait, independent of syndrome. Issue 1 (20th May 2019) - Ellis, Colin A.; Churilov, Leonid; Epstein, Michael P.; Xie, Sharon X.; Bellows, Susannah T.; Ottman, Ruth; Berkovic, Samuel F.
Abstract : Objective: We tested 2 hypotheses regarding age at onset within familial epilepsies: (1) family members with epilepsy tend to have similar ages at onset, independent of epilepsy syndrome; and (2) age at onset is younger in successive generations after controlling for sampling bias. Methods: We analyzed clinical data collected by the Epi4K Consortium (303 multiplex families, 1, 120 individuals). To test hypothesis 1, we used both linear mixed models commonly used for heritability analysis and Cox regression models with frailty terms to assess clustering of onset within families after controlling for other predictors. To test hypothesis 2, we used mixed effects models, pairwise analyses, and survival analysis to address sampling‐related bias that may mimic anticipation. Results: Regarding hypothesis 1, age at seizure onset was significantly heritable (intraclass correlation coefficient = 0.17, p < 0.001) after adjusting for epilepsy type, sex, site, history of febrile seizure, and age at last observation. This finding remained significant after adjusting for epilepsy syndromes, and was robust across statistical methods in all families and in generalized families. Regarding hypothesis 2, the mean age at onset decreased in successive generations ( p < 0.001). After adjusting for age at last observation, this effect was not significant in mixed effects models ( p = 0.14), but remained significant in pairwise ( p = 0.0003) and survival analyses ( p = 0.02). Interpretation: Age at seizure onset is an independent familial trait, and may have genetic determinants distinct from the determinants of particular epilepsy syndromes. Younger onsets in successive generations can be explained in part by sampling bias, but the presence of genetic anticipation cannot be excluded. ANN NEUROL 2019